If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(2x + 8) = 34 Reorder the terms: 8x + -1(8 + 2x) = 34 8x + (8 * -1 + 2x * -1) = 34 8x + (-8 + -2x) = 34 Reorder the terms: -8 + 8x + -2x = 34 Combine like terms: 8x + -2x = 6x -8 + 6x = 34 Solving -8 + 6x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6x = 34 + 8 Combine like terms: -8 + 8 = 0 0 + 6x = 34 + 8 6x = 34 + 8 Combine like terms: 34 + 8 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| 0.07x=70 | | 0.07x=7 | | 23x-7-18+3=20x-6-15+16 | | -2(y+5)= | | 0.07x=0.7 | | 5.7q-2.2-5.9q=-1.9q-4.3 | | 2(y+1)=2(y-4) | | .06x-x=1000 | | 3x-2=4+3x | | -4(t-3)+8t=7t-7 | | 9(t-13)=4(t-3) | | 3+7x=3x+19 | | .05x-x=1000 | | 8(t-5)=5(t+4) | | 2n+27=2711110 | | 4y=8+2y | | x+x+x-x=20 | | 7(t+42)=3(t+126) | | 6-8t=60+t | | 1+2z=5 | | X^2+20x-44=0 | | -6t+3=-6t | | 192.50+120.00= | | (4a+2)(3a-5)= | | -3(2x-4)+8x-8= | | (2t+5)(t+4)= | | =4(m-1) | | 3x^2-4y^2+x-y=0 | | 23-3(2W+1)=8W-3(8+W) | | -5(7n-4)+35n= | | z=0.125z+49 | | -3(x-4)=25 |